Effect of expanded variation in anther position on pollinator visitation to wild radish, Raphanus raphanistrum. (22nd May 2017) - Sapir, Yuval; Karoly, Keith; Koelling, Vanessa A; Sahli, Heather F; Knapczyk, Frances N; Conner, Jeffrey K
Abstract: Background and Aims Plant–pollinator interactions shape the evolution of flowers. Floral attraction and reward traits have often been shown to affect pollinator behaviour, but the possible effect of efficiency traits on visitation behaviour has rarely been addressed. Anther position, usually considered a trait that influences efficiency of pollen deposition on pollinators, was tested here for its effect on pollinator visitation rates and visit duration in flowers of wild radish, Raphanus raphanistrum . Methods Artificial selection lines from two experiments that expanded the naturally occurring phenotypic variation in anther position were used. In one experiment, plant lines were selected either to increase or to decrease anther exsertion. The other experiment decreased anther dimorphism, which resulted in increased short stamen exsertion. The hypothesis was that increased exsertion would increase visitation of pollen foragers due to increased visual attraction. Another hypothesis was that exsertion of anthers above the corolla would interfere with nectar foragers and increase the duration of visit per flower. Key Results In the exsertion selection experiment, increased exsertion of both short and long stamens resulted in an increased number of fly visits per plant, and in the dimorphism experiment bee visits increased with increased short stamen exsertion. The duration of visits of nectar feeders declined significantly with increasing long stamen exsertion, which was opposite to the hypothesis. Conclusions Until now, anther position was considered to be an efficiency trait to enhance pollen uptake and deposition. Anther position in wild radish is shown here also to have an ecological significance in attracting pollen foragers. This study suggests an additional adaptive role for anther position beyond efficiency, and highlights the multiple ecological functions of floral traits in plant–pollinator interactions.